Studies on Schismatoglottideae (Araceae) of Borneo LVI – Two new species of Schismatoglottis for the Nervosa Grade - Wong, Sin Yeng; Low, Shook Ling; Boyce, P.C (BGBM Berlin-Dahlem., 2016)
Schismatoglottis amosyui S. Y. Wong, S. L. Low & P. C. Boyce, sp. nov. and S. pocong S. Y. Wong, S. L. Low & P. C. Boyce, sp. nov. are described and illustrated as taxonomically novel species belonging to the Nervosa Grade, a paraphyletic grade defined, uniquely for Schismatoglottideae, by aromatic vegetative tissues.